Personality Traits and Self-Esteem in Combat and Team Sports - Bojanić, Željka; Nedeljković, Jasmina; Šakan, Dušana; Mitić, Petar M.; Milovanović, Ivana; Drid, Patrik (Frontiers in Psychology, 2019)
The aim of this research was to examine whether psychological variables which make up basic dimensions of personality and self-esteem distinguish competitors in combat sports from competitors in team sports. The research included 149 respondents, aged 19 to 27 years. The Self-Esteem Scale questionnaire was used to measure self-esteem. The BFI inventory was used to measure personality traits according to the Big Five model: Extraversion, Neuroticism, Conscientiousness, Agreeableness, and Openness to Experience. The basic research question is - does the set of psychological variables which make up basic dimensions of personality and self-esteem statistically significantly distinguish competitors in combat sports from the competitors in team sports? Both mean differences and simple discriminant function analyses for competitors in combat/team sports revealed that self-esteem, neuroticism, and conscientiousness were the most important factors distinguishing the two groups. Practical implications, limitations and future research directions were discussed.